1996
DOI: 10.1074/jbc.271.22.12944
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 Family Proteins Recognize the U5 Repressive Element of the Long Terminal Repeat of Human T Cell Leukemia Virus Type I through Binding to the CACCC Core Motif

Abstract: We have identified several nuclear proteins binding to the U5 repressive element (U5RE) at the U5 region of the human T cell leukemia virus type I (HTLV-I) long terminal repeat (LTR). In gel mobility shift assays with the U5RE DNA probe, Jurkat T cell nuclear proteins generated five different complexes, named U5RE binding protein complexes (U5RP)-A1, -A2, -A3, -B, and -C. Only U5RP-C was affected by pretreatment with an excess of poly(dI-dC) and was immunodepressed by anti-Ku/p80 antibodies, suggesting that U5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 49 publications
2
27
2
Order By: Relevance
“…9) We have identified a 27-bp transcriptional repressive element in the U5 region of 5′-long terminal repeat (LTR) (U5RE) to which several nuclear proteins bind -a process involving Sp1 and Sp3. 10) We also found that HUB1, a Krüppel type zinc finger protein, binds to U5RE by recognizing the TCCACCCC sequence.…”
Section: -7)mentioning
confidence: 99%
See 2 more Smart Citations
“…9) We have identified a 27-bp transcriptional repressive element in the U5 region of 5′-long terminal repeat (LTR) (U5RE) to which several nuclear proteins bind -a process involving Sp1 and Sp3. 10) We also found that HUB1, a Krüppel type zinc finger protein, binds to U5RE by recognizing the TCCACCCC sequence.…”
Section: -7)mentioning
confidence: 99%
“…10) We verified the effects of Sp1 using Drosophila SL2 cells, which are known to be devoid of endogenous Sp1 activity.…”
Section: Sp1 Activates Transcription Through U5rementioning
confidence: 99%
See 1 more Smart Citation
“…2). CACCC stretches have been shown to be important in binding to host cell transcription factors important in growth control, apoptosis, and angiogenesis (4,44) and are also utilized for double-stranded DNA virus and retroviral transcription (38,44,56). Strict maintenance of these CACCC domains was seen in all but a few known PRRSV leader sequences (Fig.…”
Section: -Leader Sequence Variationmentioning
confidence: 99%
“…These include the rat D 2 dopamine promoter (43), the rat ␣ 2 A adrenergic promoter (44), the long terminal receptor of the human T cell leukemia virus type I promoter (45), the rat fatty acid synthase promoter (46), and the rat smooth muscle myosin heavy chain promoter (47). The finding that the GC or GT box is involved in the negative regulation of gene expression implies that the GC or GT box may play a more complicated role in transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%